PENGARUH HEALTH EDUCATION DENGAN MEDIA AUDIO VISUAL TERHADAP TINDAKAN MASYARAKAT DALAM MELAKUKAN PERTOLONGAN PERTAMA PADA PASIEN STROKE - Rusli Taher; Nurhikmah; Sarina Ali; Hardianti Bugis (Stikes Graha Edukasi Makassar, 2022)
Objective: The purpose of this study was to determine the effect of health education with audio-visual media on community actions in providing first aid to stroke patients. Methods: This research design uses a one group pretest-post test design. The population in this study were all patients aged 17-35 years at the Siwaliman Health Center, Aru Islands District, Aru Islands Regency, amounting to 300 people. The sampling technique of this research is consecutive sampling so that the research sample is 45 people. The research instrument used the Extension Program Unit, and a questionnaire. Data analysis using Wilcoxon Signed Rank Test. Results: The results of this study indicate that most respondents had negative actions before being given health education with audiovisual media, namely 32 people (71.1%), and almost all respondents had positive actions after being given health education with audiovisual media, namely 43 people ( 95.6%). The results of the Wilcoxon test analysis obtained a p value of 0.000 less than (0.05) so that H1 was accepted, which means that there is an effect of health education with audiovisual media on first aid actions for stroke patients at the Siwaliman Health Center, Aru Islands District, Aru Islands Regency. Conclusion: The conclusion from the results of this study shows that there is an effect of health education with audio-visual media on community actions in providing first aid to stroke patients. Suggestion: The community is expected to take part in emergency training, especially first aid for stroke patients as a preventive effort to prevent disability due to delays in pre-hospital stage assistance